"To clip or not to clip. That is no question!" - Aznar, M; Meattini, I; Poortmans, P; Steyerova, P; Wyld, L (Elsevier, 2017)
Breast conservation surgery (BCS) followed by radiation therapy (RT) is the local treatment of choice for an increasing percentage of women with breast cancer (BC). Surgical techniques for contemporary breast conservation are sophisticated and sensitive to aesthetic considerations.